Asymmetry in Membrane Responses to Electric Shocks: Insights from Bidomain Simulations - Ashihara, Takashi (Biophysical Society, 2004)
Models of myocardial membrane dynamics have not been able to reproduce the experimentally observed negative bias in the asymmetry of transmembrane potential changes (ΔV(m)) induced by strong electric shocks delivered during the action potential plateau. The goal of this study is to determine what membrane model modifications can bridge this gap between simulation and experiment. We conducted simulations of shocks in bidomain fibers and sheets with membrane dynamics represented by the LRd'2000 model. We found that in the fiber, the negative bias in ΔV(m) asymmetry could not be reproduced by addition of electroporation only, but by further addition of hypothetical outward current, I(a), activated upon strong shock-induced depolarization. Furthermore, the experimentally observed rectangularly shaped positive ΔV(m), negative-to-positive ΔV(m) ratio (asymmetry ratio) = ∼2, electroporation occurring at the anode only, and the increase in positive ΔV(m) caused by L-type Ca(2+)-channel blockade were reproduced in the strand only if I(a) was assumed to be a part of K(+) flow through the L-type Ca(2+)-channel. In the sheet, I(a) not only contributed to the negative bias in ΔV(m) asymmetry at sites polarized by physical and virtual electrodes, but also restricted positive ΔV(m). Inclusion of I(a) and electroporation is thus the bridge between experiment and simulation.